2017
DOI: 10.18321/ectj683
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of Low-Energy-Intensive Technology of Receiving Sulphate-Resistant and Road Portlandcement

Abstract: The article presents the obtaining results of clinkers of sulfate resistant and road cement during the production tests process. The usage of man-made wastes such as lead slag, coal mining waste as well as clay component and additives. X-ray, chemical analyzes of starting materials, clinkers and obtained cements were carried out. The regularities of charge compositions, saturation coefficient, modules, burning regimes on chemical and mineralogical composition and quality of clinkers and cements, improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…Non-standard reaction (10) proceeded in the entire investigated temperature range, having negative Gibbs energies from −898.9 kJ to −20,066.2 kJ, respectively, having a significant advantage over the standard reaction (6). The data obtained were consistent with the research carried out by a number of scientists [ 25 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] and complement them. Regarding the distillation of non-ferrous metals, in particular, zinc, in the simulated reactions, it was shown that non-ferrous metals in the form of zinc are able to pass into the gas phase and be captured in bag filters.…”
Section: Discussionsupporting
confidence: 89%
“…Non-standard reaction (10) proceeded in the entire investigated temperature range, having negative Gibbs energies from −898.9 kJ to −20,066.2 kJ, respectively, having a significant advantage over the standard reaction (6). The data obtained were consistent with the research carried out by a number of scientists [ 25 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] and complement them. Regarding the distillation of non-ferrous metals, in particular, zinc, in the simulated reactions, it was shown that non-ferrous metals in the form of zinc are able to pass into the gas phase and be captured in bag filters.…”
Section: Discussionsupporting
confidence: 89%
“…The essence of regularization is to impose additional constraints on various parameters or to add a priori information, thus reducing the model error as its complexity increases [19,20].…”
Section: Using Big Data To Develop Multi-dimensional and Regularized Regression Modelsmentioning
confidence: 99%
“…Industrial waste located in dumps and containing in its chemical composition heavy non-ferrous metals and various compounds of silicon, calcium, aluminum and iron has a negative impact on the environment from the point of view of ecology, in particular on public health, flora and fauna [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. However, based on its chemical composition, it is valuable and can serve as a secondary technogenic raw material for various kinds of industries, for example in the metallurgical, construction, chemical and other industries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 …”
Section: Introductionmentioning
confidence: 99%
“…However, based on its chemical composition, it is valuable and can serve as a secondary technogenic raw material for various kinds of industries, for example in the metallurgical, construction, chemical and other industries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Thus, in Kazakhstan, in the process of extracting non-ferrous metals at a number of plants, since the 1920s and up to the present, in a number of areas, in particular, in the east Kazakhstan and Turkestan regions, there is a significant amount of clinker waste from the cultivation of various raw materials, which is now stored in dumps, occupying fertile lands and polluting the soil, surface and groundwater, the atmosphere, penetrating animal and human organisms through the migration of heavy metals along the food chain [ 9 ,…”
Section: Introductionmentioning
confidence: 99%